Thermal Characteristics Evaluation of Vegetables Oil to be Used as Phase Change Material in Air Conditioning System - Yuli S. Indartono; Aryadi Suwono; Ari D. Pasek; Didin Mujahidin; Irfansyah Rizal (Jurnal Teknik Mesin (Sinta 3), 2010)
In a typical commercial building, air conditioning system consumes around 60% of building’s electricity. By looking at that number, it is clear that effort to suppress building energy consumption should be directed to air conditioning system. Recently, phase change substances, such as ice slurry, receive broad attention since the substances has ability to save energy in hydronic cooling system. Previous experiments by author showed that certain phase change material, i.e. trimethylolethane trihydrate, is able to save energy of a chiller. However, in Indonesia, the material is quite expensive. In this research, applicability of some lower-price materials, i.e. mixture of vegetables oil and biodiesel, as phase change material in secondary refrigerant were evaluated. Some thermal characteristics, such as freezing and melting temperatures, and also latent heat of the oils are explained in this paper.